Development of the national feral swine map, 1982–2016 - Joseph L. Corn; Thomas R. Jordan (Wildlife Society Bulletin)
ABSTRACT The Southeastern Cooperative Wildlife Disease Study developed the first national feral swine (Sus scrofa) map for the United States in 1982 in collaboration with state wildlife resources agencies. National feral swine distribution maps were completed in 1982, 1988, and 2004 as individual maps, and then annually beginning in 2008 through the National Feral Swine Mapping System (NFSMS). The NFSMS is an internet‐based data‐collection website used in collaboration with state wildlife resources agencies and the U.S. Department of Agriculture, Animal and Plant Health Inspection Service. These ongoing collaborations have provided for a long‐term database that documents the expansion of established feral swine populations in the United States. The number of states reporting established populations was 18 in 1982 and 35 in 2016. The geographic area included in the distribution of feral swine increased from 544,854 km2 in 1982 to 1,675,618 km2 in 2016. We describe the development of the national feral swine maps including details on how these data were collected; provide feral swine maps for select years from 1982 to 2016; and note some of the uses of these maps. These maps detail the expansion of feral swine since 1982, which can be used in the future to monitor increases or decreases in the distribution of feral swine as natural reproduction of feral swine continues and feral swine control programs are implemented. © 2017 The Wildlife Society.